MENGEMBANGKAN KARAKTER TANGGUNG JAWAB PADA PEMBELAJAR (Perspektif Psikologi Barat Dan Psikologi Islam) - Elfi Yuliani Rochmah (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2016)
Abstrak: Character of responsibility is not something that is automatic in the learners, we have to understand is that the potential positive and negative is always there in every individual human being grows and develops. The attitude and behaviour of responsibility need to be built and conditioned as necessities of life to complement its growth and development of individuals reach maturity its fullest potential. This paper attempted to examine the responsibility as an attitude and behavior that became part of the character of learners. Cultivate and develop the attitudes and behaviors of liability is part of character education are continually strived and developed the character to be attached to the individual. In turn, it is expected they will have a positive winning character as future generations of people.Keywords; Attitude, Responsibility, Character, Aspects Of Development